Bridging the gaps for a thriving Black Sea Blue Economy: insights from a multi-sectoral forum of Turkish stakeholders - Kadir Seyhan; Ömerhan Dürrani; Lydia Papadaki; Ebun Akinsete; Şebnem Atasaral; Koray Özşeker; Hatice Akpınar; Ercan Kurtuluş; Rahşan Evren Mazlum; Phoebe Koundouri; Phoebe Koundouri; Phoebe Koundouri; et al. (Frontiers in Marine Science)
The Black Sea ecosystem faces significant challenges due to climate change and human activities. Despite this, the opportunities and potential of its Blue Economy and the role of Turkish stakeholders in the key sectors have not been well documented. To define the needs of the Black Sea’s Blue Economy and outline existing problems, a workshop entitled “Engaging Stakeholders: Trabzon Multi-Actor Forum” was held in Trabzon (Türkiye) in November 2022. Stakeholders from the research sector, academia, civil society, industry, business, competent authorities, and government shared their thoughts on various sectors of the Blue Economy, covering 17 areas. They discussed political, environmental, social, technical, legal, and economic aspects, revealing opportunities, challenges, and areas where more research is needed. This meeting provided valuable insights, indicating that efficient collaboration with stakeholders could lead to effective solutions and strategies, helping to improve the Blue Economy in the Black Sea region.